Estimating P- and S-Wave Velocities in Fluid Mud Using Seismic Interferometry - Ma, Xu; Kirichek, Alex; Heller, Karel; Draganov, Deyan (Frontiers in Earth Science, 2022)
Fluid mud plays an important role in navigability in ports and waterways. Characterizing and monitoring the seismic properties of fluid mud can help understand the geotechnical behavior of fluid mud. Estimation of the wave velocities in fluid mud with high accuracy and repeatability enables investigating the geotechnical behavior such as the yield stress of the fluid mud in a nonintrusive and reliable way. We perform ultrasonic reflection measurement in a laboratory to investigate the wave propagation in a water/fluid-mud layered system. The component of wave propagation in the water layer inevitably brings kinematic dependence on the characteristics of that layer, making the estimation of exact velocities in fluid mud more challenging. In order to extract the wave velocities only in the fluid-mud layer, we use a reflection geometry imitating field measurement to record the ultrasonic data from sources and receivers in the water layer. We then use seismic interferometry to retrieve ghost reflections from virtual sources and receivers placed directly at the water-mud interface. Using velocity analysis applied to the ghost reflections, we successfully obtain the P-wave and S-wave velocities only inside the fluid-mud layer, and investigate the velocity change during the self-weight consolidation of the fluid mud. Our results indicate that the S-wave velocities of the fluid mud increase with consolidation time, and show that reflection measurements and ghost reflections can be used to monitor the geotechnical behavior of fluid mud.